1992
DOI: 10.1161/01.hyp.20.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Brain atrophy in hypertension. A volumetric magnetic resonance imaging study.

Abstract: To determine whether hypertension, the predominant risk factor for stroke and vascular dementia, is associated with brain atrophy, magnetic resonance imaging (MRI) scans were performed to quantify brain volumes and cerebrospinal fluid spaces. Eighteen otherwise healthy, cognitively normal older hypertensive men (mean±SD age, 69±8 years, duration of hypertension 10-35 years) and 17 age-matched healthy, normotensive male control subjects were studied in a cross-sectional design. Axial proton-density image slices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
112
3

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 67 publications
3
112
3
Order By: Relevance
“…22 We believe this study provides the first estimate of the heritability of brain atrophy, which is another recognized risk factor for cognitive impairment in the elderly. 5,23,24 The bivariate linkage analyses of brain atrophy and PP provided the strongest evidence of genes with pleiotropic effects on measures of BP and brain injury. Of the regions on chromosomes 11 and 16 that satisfied the bivariate criteria for significant evidence of linkage, the chromosome 11p15 region was detected in the univariate linkage analyses of PP but not brain atrophy, whereas the chromosome 16q region was detected in the univariate linkage analyses of brain atrophy but not PP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 We believe this study provides the first estimate of the heritability of brain atrophy, which is another recognized risk factor for cognitive impairment in the elderly. 5,23,24 The bivariate linkage analyses of brain atrophy and PP provided the strongest evidence of genes with pleiotropic effects on measures of BP and brain injury. Of the regions on chromosomes 11 and 16 that satisfied the bivariate criteria for significant evidence of linkage, the chromosome 11p15 region was detected in the univariate linkage analyses of PP but not brain atrophy, whereas the chromosome 16q region was detected in the univariate linkage analyses of brain atrophy but not PP.…”
Section: Discussionmentioning
confidence: 99%
“…Both brain traits have been associated with hypertension and with cognitive dysfunction. 5,6 Moreover, measures of brain anatomy and ischemic brain injury appear to be heritable. 2,7 In addition to performing genome-wide univariate linkage analyses, we leveraged the power of multivariate linkage analyses by also conducting bivariate linkage analyses of each brain measure with a measure of steady-state BP level, ie, mean arterial pressure (MAP), and a measure of the pulsatile component of BP, ie, pulse pressure (PP).…”
mentioning
confidence: 99%
“…Hypertension has been associated with changes in brain structure and cognitive function [40][41][42][43]. It is known that hypertension accelerates the decline in cerebral perfusion [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that faster rates of ventricular expansion may be associated with AD pathology, APOE ε-4 carrier status, and cardiovascular risk factors such as hypertension and diabetes [3,8,31,35,12,29,2,25,15]. However, since most previous studies measure ventricular volume at one or two time points per subject, they are limited in the information they can provide about the time course of ventricular expansion.…”
Section: Introductionmentioning
confidence: 99%